The ‘Better for you’ concept: Leveraging the opportunities in spice value chain - V K, Sajesh; Thomas, Lijo; S R, Maneesha; Anees K (Indian Horticulture, 2025)
The global shift toward health-conscious consumption has positioned spices not only as culinary essentials but as functional ingredients aligned with the ’Better for you’ food trend. This paper explores how health-driven consumer demand presents strategic opportunities across the spice value chain, particularly for small-scale farmers, Self-Help Groups (SHGs), and Farmer Producer Organizations (FPOs). By leveraging traditional knowledge, collective action, and partnerships with Micro, Small and Medium Enterprises (MSMEs), producers can add value, improve incomes, and access premium market. The study highlights value addition methods, supply chain best practices for preserving bioactive compounds, and innovations such as spice-based wellness products. Emphasis is placed on standardization, traceability, and clean-label marketing to meet evolving consumer expectations. The integration of scientific validation with indigenous practices creates potential for sustainable and inclusive growth. Ultimately, spices are transitioning from basic commodities to high-value, health-promoting foods, offering a viable pathway to empower rural communities and reshape the global spice industry toward a more equitable future.